The Enhancement of Space Function as Ecofarming at the Underpass of Becakayu Toll Road (Bekasi Cawang Kampung Melayu) - Indrawati, Etty; Yuslim, Silia; Seanders, Olivia; Purwaningrum, Pramiati; Zahra, Annisa (MultiTech Publisher, 2024)
The existence of the becakayu toll road overpass creates open space under the road that needs to be managed because it makes the environment dirty, dusty, irregularly planted, and useless. This research aims to identify open space under the becakayu toll road as a basis for determining the eco-farming zone. The research method used is descriptive qualitative using field observations, interviews, literature studies, and documentation. The results showed that the current utilization of the becakayu toll road is not well organized (70%). Used as greening (50%), used as parking (20%), used as a sidewalk for skateboarding and cycling activities (17%), used as a fish pond (10%), and used as a place to sell (20%). From this study, the becakayu toll road can be utilized as an eco-farming area (93%). The benefit of this research is that the space under the becakayu toll road will be organized and efficiently used for the needs of the community and the surrounding environment.